Conservation and production responses vary by disturbance intensity in a long‐term forest management experiment. Issue 7 (26th May 2020) - Kroll, Andrew J.; Springford, Aaron; Verschuyl, Jake
Abstract: Reductions in management intensity are often proposed to support a broader range of beneficial ecosystem responses than traditional management approaches . However, few studies evaluate ecosystem responses across approaches. Also, managers lack information about how species traits mediate responses across management approaches, a potentially substantial source of spatial and temporal variation in population and community responses that if ignored may hinder effectiveness of management programs. We used data collected over eight years from a manipulative experiment to test how four forest management strategies influenced avian community composition and wood production. After harvesting, we evaluated responses to three levels of plant cover suppression (Light, Moderate, and Intensive herbicide applications) in relation to a control without herbicide. We predicted the Moderate and Intensive treatments would exert strong negative effects on leaf‐gleaning insectivores, including species of conservation concern due to long‐term population declines. However, given high forest productivity, we expected temporal duration of effects to be short. Richness of leaf‐gleaning bird species was reduced by 20–50% during the first four years post‐harvest (when herbicide treatments were on‐going), but the effect size declined over the next four years once treatments were completed (13–20% reduction). Effect sizes were substantially smaller for the non‐leaf‐gleaner group during years 1–4 (19–27%) and disappeared during years 5–8 (2–3%). However, in our final year of observation, we did find an average of five fewer non‐leaf‐gleaner species on Light vs. Control units. In the last two years of observation, turnover probabilities for the leaf‐gleaner species remained higher on all treatments compared to the Control (0.11–0.21), indicating that new species continued to colonize treatments. Planted conifers were 40–44% taller and 74–81% larger in diameter in the Moderate and Intensive treatments compared to the Control, leading to substantial gains in wood biomass. Current practices provided more balance between two ecosystem responses, avian diversity and wood production, compared to less intensive alternatives. When short‐term negative effects occur, the spatial distribution of harvesting and regeneration regionally indicates that habitat is often available locally to support leaf‐gleaning and non‐leaf‐gleaning bird populations while releasing other portions of the region for high priority conservation objectives including late‐successional forest reserves.